Cancellation of Sale-Purchase Agreement and Absolute Power of Attorney Clause Made Based on Debts and Receivables - Sriwati, Sriwati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The Sale and Purchase Agreement (hereinafter abbreviated to PPJB) is a preliminary agreement as an effort to overcome the obstacles of the parties who have not been able to make a Deed of Sale and Purchase (hereinafter abbreviated to AJB). However, in several cases abuse of the use of PPJB and Power of Sale has been found. PPJB and Power of Sale become a security agreement for debts. The PPJB contains a power of sale clause and a Power of Sale Deed which grants power from the owner of the land object (as the seller/party who has the debt/debtor) to the debtor (as the buyer/party who gives the receivable/creditor) to transfer land rights. Debtors who suffer losses because they do not intend to sell the land can file an effort to cancel the agreement. Based on the problem approach (statute approach), conceptual approach (conceptual approach), and case approach (case approach), namely various decisions that have legal force, it can still be concluded that the Supreme Court and lower courts have maintained the unity of law application and consistency of decisions, especially regarding legal smuggling. Sale-Purchase Agreements and Absolute Power of Attorney Clauses Made Based on Debts and Receivables, by declaring such agreements null and void by law even if the agreement is made based on a Notarial Deed or Authentic Deed. Application for cancellation of agreement due to fraud, coercion or abuse of circumstances (misbruik van omstandigheden).